Alpha-B-Crystallin Effect on Mature Amyloid Fibrils: Different Degradation Mechanisms and Changes in Cytotoxicity - Stepanenko, Olga V. (Int J Mol Sci, 2020)
Given the ability of molecular chaperones and chaperone-like proteins to inhibit the formation of pathological amyloid fibrils, the chaperone-based therapy of amyloidosis has recently been proposed. However, since these diseases are often diagnosed at the stages when a large amount of amyloids is already accumulated in the patient’s body, in this work we pay attention to the undeservedly poorly studied problem of chaperone and chaperone-like proteins’ effect on mature amyloid fibrils. We showed that a heat shock protein alpha-B-crystallin, which is capable of inhibiting fibrillogenesis and is found in large quantities as a part of amyloid plaques, can induce degradation of mature amyloids by two different mechanisms. Under physiological conditions, alpha-B-crystallin induces fluffing and unweaving of amyloid fibrils, which leads to a partial decrease in their structural ordering without lowering their stability and can increase their cytotoxicity. We found a higher correlation between the rate and effectiveness of amyloids degradation with the size of fibrils clusters rather than with amino acid sequence of amyloidogenic protein. Some external effects (such as an increase in medium acidity) can lead to a change in the mechanism of fibrils degradation induced by alpha-B-crystallin: amyloid fibers are fragmented without changing their secondary structure and properties. According to recent data, fibrils cutting can lead to the generation of seeds for new bona fide amyloid fibrils and accelerate the accumulation of amyloids, as well as enhance the ability of fibrils to disrupt membranes and to reduce cell viability. Our results emphasize the need to test the chaperone effect not only on fibrillogenesis, but also on the mature amyloid fibrils, including stress conditions, in order to avoid undesirable disease progression during chaperone-based therapy.